PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN MENYELESAIKAN SOAL GEOMETRI PADA MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA FPMIPA IKIP PGRI BALI TAHUN AKADEMIK 2015/2016 - I Made Surat (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
This study aimed to determine the effect of Problem Based Learning upon the ability to solve problems of Geometry and how the level of activity the student’s of Mathematics Department, FPMIPA IKIP PGRI Bali. This type of research is quasi eksperiment, by design matching post test only control group. From the population of 133 people taken from a sample of the research of 2 classes. There are 31 pairs of sample as a group eksperimen and control. In the group eksperiment given PBL and group control given a convensional learning. After 4 meeting, the data collected with the test and observation sheet. The technique of analisis data used for test hipotesis by t-test technique for correlated samples, at significant level 5 % for df = 30. To analyze the activity level used descriptive analysis. The analysis result obtained t-test = 3,84, confirm with t-table = 2,042 evidently t-test > t-table, this means Ho rejected and Ha accepted. So that the conclusion of this research: there is an effect of PBL toward ability to solve problems of Geometriy, and the student’ learning activity in category ‘active’. The finding of this research is recommended that the mathematic teachers implement PBL in the suitable mathematic teaching process.